KONFLIK KEPEMILIKAN TANAH MASYARAKAT MUSLIM KAMPUNG BUGIS SERANGAN BALI TAHUN 2017 - Hidayati, Firdha; Andreas Noak, Piers; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2019)
ABSTRACT This study aims to find out how conflicts over land ownership in Kampung Bugis can occur. This study uses conflict theory by Lewis A. Coser and uses descriptive qualitative methods.The results of this study indicate that: first, the conflict between the people of Kampung Bugis with the heirs has occurred since 2008 and re-emerged in 2012 after the ruling from the Supreme Court (MA) cassation No.3081/PDT/2012 for ownership of the land. Secondly, the conflict occurred due to unclear ownership status and land boundaries, differences in the purpose of land use and the lack of community knowledge regarding laws and regulations regarding land issues, especially regarding the procedure for making land certificates. Third, efforts to resolve it through dialogue with related parties have been made but there is no agreement yet. Settlement efforts came from the Bali Turtle Island Development (BTID) as the developer of the Serangan Island area. Keywords : Conflict, Society, Conflict Resolution and Impact